COLLABORATIVE GOVERNANCE STRATEGY (PRO-COLEGA) IN REALIZING SUSTAINABLE INDUSTRIAL RELATIONS HARMONIZATION: THE ROLE OF OMBUDSMAN IN SUPERVISION AND MEDIATION - Muhammad Farhan Diaz Fahreza; Adi Suhendra (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2026)
This study examines the implementation of the Collaborative Governance strategy (PRO-COLEGA) in realizing sustainable industrial relations harmonization, with a particular focus on the role of the Ombudsman in supervision and mediation. This research employs a qualitative case study approach conducted in Bekasi City, selected due to its high intensity of industrial relations disputes and recurring public complaints in the labor sector. Data were collected through in-depth interviews with key stakeholders (labor mediators, trade union representatives, employers, and Ombudsman officials), document analysis, and secondary data from Ombudsman RI reports. The findings reveal four key themes: (1) low inter-stakeholder trust, (2) institutional capacity limitations in mediation, (3) procedural inconsistencies in dispute resolution, and (4) the strategic yet constrained role of the Ombudsman in collaborative governance. The study demonstrates that PRO-COLEGA contributes to strengthening industrial relations only when supported by clear role distribution, effective mediation capacity, and sustained stakeholder commitment. This research refines the PRO-COLEGA model by specifying its actors, process flow, expected outcomes, and boundary conditions, thereby contributing empirically to the collaborative governance literature in the context of industrial relations.